Analisis Kesalahan Siswa dalam Menyelesaikan Soal Cerita Pecahan pada Siswa Kelas VI Di Sekolah Dasar Kartika XVII-1 Pontianak Kota - Hani Alwandita (Departement of Mathematics Education, 2024)
Abstract This research aims to analyze the types of errors made by class VI students at the Kartika XVII-1 Pontianak City Elementary School in solving fraction story problems. The research method used is a mixed method. The data sources in this study were 27 students in class VI at Kartika XVII-1 Elementary School. Data collection techniques in this research were observation, tests in the form of student answers and interviews with teachers and students. The results of this research were that students made reading errors 15 times (8.72%), errors in understanding the questions 80 times (46.51%), transformation errors 16 times (9.30%), calculation process errors 36 times. (20.93%), and errors in writing the final answer 25 times (14.53%). The factors that cause students to make mistakes are internal factors or factors within the student, namely due to carelessness (forgetting, not being thorough and rushing), not understanding the questions and not understanding the material. Keywords: the analysis of error, mathematics word problem. Abstrak Penelitian ini bertujuan untuk menganalisis jenis kesalahan yang dilakukan siswa kelas VI di Sekolah Dasar Kartika XVII-1 Pontianak Kota dalam menyelesaikan soal cerita pecahan. Metode penelitian yang digunakan adalah metode campuran. Sumber data dari penelitian ini adalah 27 siswa kelas VI SD Kartika XVII-1. Teknik pengumpulan data pada penelitian ini adalah observasi, tes berupa hasil jawaban siswa dan wawancara dengan guru dan siswa. Hasil dari penelitian ini adalah siswa melakukan kesalahan membaca sebanyak 15 kali (8,72%), kesalahan memahami soal sebanyak 80 kali (46,51%), kesalahan transformasi sebanyak 16 kali (9,30%), kesalahan proses perhitungan sebanyak 36 kali (20,93%), dan kesalahan penulisan jawaban akhir sebanyak 25 kali (14,53%). Faktor penyebab siswa melakukan kesalahan adalah faktor internal atau faktor dari dalam diri siswa yaitu karena kecerobohan (lupa, tidak teliti dan terburu- buru), tidak memahami soal dan tidak memahami materi. Kata kunci: Kesalahan siswa, Soal cerita pecahan.